Comparison of the Pullout Strength of Different Pedicle Screw Designs and Augmentation Techniques in an Osteoporotic Bone Model - BEZER, MURAT (KOREAN SOC SPINE SURGERY, 2018)
Study Design: Mechanical study. Purpose: To compare the pullout strength of different screw designs and augmentation techniques in an osteoporotic bone model. Overview of Literature: Adequate bone screw pullout strength is a common problem among osteoporotic patients. Various screw designs and augmentation techniques have been developed to improve the biomechanical characteristics of the bone-screw interface. Methods: Polyurethane blocks were used to mimic human osteoporotic cancellous bone, and six different screw designs were tested. Five standard and expandable screws without augmentation, eight expandable screws with polymethylmethacrylate (PMMA) or calcium phosphate augmentation, and distal cannulated screws with PMMA and calcium phosphate augmentation were tested. Mechanical tests were performed on 10 unused new screws of each group. Screws with or without augmentation were inserted in a block that was held in a fixture frame, and a longitudinal extraction force was applied to the screw head at a loading rate of 5 mm/min. Maximum load was recorded in a load displacement curve. Results: The peak pullout force of all tested screws with or without augmentation was significantly greater than that of the standard pedicle screw. The greatest pullout force was observed with 40-mm expandable pedicle screws with four fins and PMMA augmentation. Augmented distal cannulated screws did not have a greater peak pullout force than nonaugmented expandable screws. PMMA augmentation provided a greater peak pullout force than calcium phosphate augmentation. Conclusions: Expandable pedicle screws had greater peak pullout forces than standard pedicle screws and had the advantage of augmentation with either PMMA or calcium phosphate cement. Although calcium phosphate cement is biodegradable, osteoconductive, and nonexothermic, PMMA provided a significantly greater peak pullout force. PMMA-augmented expandable 40-mm four-fin pedicle screws had the greatest peak pullout force.
Keywords: Screw; Pedicle; Expandable; Osteoporosis; Augmentation; POLYMETHYLMETHACRYLATE AUGMENTATION; CEMENT AUGMENTATION; SPINAL SURGERY; FIXATION; VERTEBRAE; INJECTION